Method for preparing wafer-level ultra-smooth laminated monocrystalline boron nitride film
Patent Information
- Application Number
- CN202511579759.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-10-31
AI Technical Summary
(1)界面污染:传统湿法转移过程中使用的聚合物(如PMMA)残留会导致层间界面污染,严重影响器件的电学性能
[0030]本发明制备的叠层单晶氮化硼薄膜的层数可控、界面洁净、角度可控。通过干法贴合,避免了氮化硼界面与聚合物和溶剂直接接触,减少了二维材料界面污染物的存在。同时,基于制备的超平整单晶氮化硼具有极高的平整度,避免了干法贴合过程中褶皱、台阶等导致的局部破损,能够有效保证最终叠层氮化硼薄膜的完整度。
Smart Images

Figure CN121272548B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of two-dimensional material preparation, specifically to a method for preparing wafer-level ultra-flat stacked single-crystal boron nitride thin films. Background Technology
[0002] In recent years, two-dimensional materials have shown great application potential in fields such as electronic devices, optoelectronic devices, and quantum computing due to their unique physical and chemical properties. Hexagonal boron nitride (h-BN), as a typical two-dimensional insulating material, possesses an atomically flat surface, high thermal conductivity (350~600 W / m·K), wide bandgap (~6 eV), and excellent chemical stability, making it considered an ideal dielectric layer, encapsulation material, and substrate material. However, the controllable preparation of high-quality few-layer (2-10 layer) single-crystal h-BN thin films still faces significant challenges.
[0003] Currently, the preparation of few-layer h-BN thin films mainly relies on direct growth via chemical vapor deposition (CVD) or mechanical exfoliation. While CVD direct growth can achieve the synthesis of large-area h-BN films, the flatness, single crystallinity, and layer uniformity are difficult to precisely control during multilayer growth, leading to layer inhomogeneity and grain boundary defects, which severely affect the film's crystal quality and electrical properties. For example, studies have shown that in metals such as iron and nickel, where B and N atoms have high solubility, it is difficult to achieve uniform segregation in multilayer h-BN films grown by CVD. Simultaneously, the lattice symmetry mismatch between the substrate and boron nitride prevents the acquisition of single-crystal boron nitride films. Polycrystalline boron nitride, due to the presence of grain boundaries and defects, cannot meet the application requirements for gate dielectrics and encapsulation layers. Although mechanical exfoliation can obtain high-quality single-crystal h-BN wafers, it suffers from uncontrollable layer number, size limitations (typically <100 μm), and poor repeatability, making it difficult to meet the needs of large-scale applications.
[0004] Stacking and constructing few-layer boron nitride (BN) films by transferring single-layer monocrystalline boron nitride is another method for preparing BN films. In recent years, significant breakthroughs have been achieved in the fabrication of single-layer monocrystalline boron nitride wafers (such as the realization of wrinkle-free, ultra-flat single-crystalline boron nitride wafers based on strong interfacial coupling), making the fabrication of large-area two-dimensional materials possible (Wang, Y. Nature Materials, 23(11), 1495-1501.). However, the following key problems still exist in the layer-by-layer stacking and construction of few-layer h-BN films: (1) Interface contamination: Residual polymers (such as PMMA) used in traditional wet transfer processes can lead to interlayer interface contamination, which seriously affects the electrical performance of the device.
[0005] (2) Mechanical damage: Stress during the transfer process may cause film wrinkles, cracks or uneven interlayer spacing, which may damage the intrinsic properties of h-BN.
[0006] Therefore, developing a method for constructing few-layer h-BN thin films that can precisely control the number of layers, maintain single-crystal properties, avoid interface contamination, and achieve high flatness is crucial for promoting the application of two-dimensional materials in high-end electronic devices. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing wafer-level ultra-flat stacked single-crystal boron nitride thin films.
[0008] This invention first provides a method for preparing wafer-level stacked single-crystal boron nitride thin films, comprising the following steps: (1) A polymer transfer medium is spin-coated on a wafer-level monolayer single-crystal boron nitride wafer, and then the copper-nickel alloy on the wafer-level monolayer single-crystal boron nitride wafer is etched away to obtain a monolayer single-crystal boron nitride thin film. (2) The wafer-level stacked monocrystalline boron nitride film is obtained by stacking single-layer monocrystalline boron nitride films by a dry lamination method of layer transfer.
[0009] The above preparation method, step (1) specifically includes the following steps: spin-coating a layer of camphor on a wafer-level monolayer single-crystal boron nitride wafer, and then spin-coating a layer of polymethyl methacrylate; after the polymethyl methacrylate has cured, it is placed in an ammonium persulfate solution to etch away the copper-nickel alloy on the wafer-level monolayer single-crystal boron nitride wafer, so that the boron nitride and the substrate are separated, and a monolayer single-crystal boron nitride thin film is obtained; Alternatively, step (1) specifically includes the following steps: spin-coating a layer of polymethyl methacrylate onto a wafer-level monolayer monocrystalline boron nitride wafer; after the polymethyl methacrylate has cured, placing it in an ammonium persulfate solution to etch away the copper-nickel alloy on the wafer-level monolayer monocrystalline boron nitride wafer, thereby separating the boron nitride from the substrate and obtaining a monolayer monocrystalline boron nitride thin film.
[0010] In the above preparation method, step (1) involves baking the polymethyl methacrylate at 150-180°C for 5-10 minutes after spin-coating. The concentration of the ammonium persulfate solution is 1~2 mol / L; During spin coating, the borneol solution used has a mass percentage concentration of 20-30%, and the polymethyl methacrylate solution has a mass percentage concentration of 4-10%.
[0011] The above preparation method, step (2) specifically includes the following steps: using polydimethylsiloxane tape to bond the single-layer single-crystal boron nitride film obtained in step (1) to another wafer-level single-layer single-crystal boron nitride wafer through a roller press; after releasing the polydimethylsiloxane tape, a composite structure is obtained; then the composite structure is placed in ammonium persulfate solution to etch away the copper-nickel alloy, and a double-layer single-crystal boron nitride film is obtained; repeat the above steps until a stacked single-crystal boron nitride film with a specified number of layers is obtained, and finally the polymer transfer medium is removed to obtain the wafer-level stacked single-crystal boron nitride film.
[0012] In the above preparation method, in step (2), the polydimethylsiloxane tape is released by heating to 150~180℃; The polymer transfer medium (borneol and polymethyl methacrylate, or polymethyl methacrylate) in the composite structure was removed by soaking in acetone at 75~80℃. The concentration of the ammonium persulfate solution is 1~2 mol / L.
[0013] The above-mentioned preparation method also includes a step of transferring wafer-level stacked single-crystal boron nitride thin films onto the target substrate.
[0014] The above-described preparation method for fabricating a wafer-level monolayer single-crystal boron nitride wafer includes the following steps: S1. Heat the ammonia borane powder in a hydrogen atmosphere at 120~140℃ to obtain ammonia borane with a stalactite-like structure. S2. Using the stalactite-like structured ammonia boronane crop precursor, a boron nitride thin film is prepared by chemical vapor deposition.
[0015] In the preparation method described above, the heating treatment time in step S1 is 10-15 min; specifically, it can be 10 min. The temperature of the heat treatment is 130±5℃.
[0016] The preparation method described above includes the following steps in step S1: placing ammonia borane powder at the bottom of the inner sleeve of a double-layered tube, turning the opening of the outer sleeve toward the gas inlet, introducing hydrogen gas, and heating to 130±5℃ for treatment to obtain ammonia borane with a stalactite-like structure.
[0017] In the above preparation method, the double-layered tube includes an inner tube and an outer tube, both of which are test tubes open at one end; the outer tube is fitted over the inner tube, and the opening directions of the outer tube and the inner tube are opposite. The diameter ratio of the inner sleeve to the outer sleeve is 1:2 to 3:4; The outer sleeve is longer than the inner sleeve.
[0018] In the above preparation method, the hydrogen gas flow rate is 300~500 sccm; specifically, it can be 500 sccm. The system pressure is 200~300 Torr; specifically, it can be 200 Torr.
[0019] Step S1 also includes the step of heating and then cooling to room temperature; During the cooling process, the introduced gas is replaced with a mixture of argon and hydrogen; the system pressure is atmospheric pressure. Specifically, in the mixed gas, the volume ratio of argon to hydrogen can be from 1:1 to 3:1; specifically, it can be 2:1. The flow rate of the mixed gas can be 500~2000 sccm; specifically, it can be 1000 sccm.
[0020] In the above preparation method, step S2 involves chemical vapor deposition on a wafer-level copper-nickel alloy wafer.
[0021] The above-described preparation method for a wafer-level copper-nickel alloy single-crystal wafer includes the following steps: (1) The c-axis single-sided polished sapphire wafer is subjected to high-temperature annealing in a pure oxygen atmosphere; (2) A nickel film was deposited on the surface of a single-sided polished sapphire wafer in the c-direction after annealing by magnetron sputtering; (3) A copper thin film is deposited on the nickel thin film described in step (2) by magnetron sputtering to obtain a wafer with a copper-nickel thin film deposited on it; (4) Load multiple wafers with deposited copper-nickel thin films into a slot-type wafer carrier, and then perform high-temperature annealing to obtain the copper-nickel alloy single crystal wafer; The slotted wafer carrier is a frame-type container made of quartz material; the inner wall of the frame of the slotted wafer carrier is provided with parallel slots for inserting quartz plates. The wafer with the deposited copper-nickel thin film is placed on a quartz plate, and a graphite is placed between the wafer and the quartz plate to support the wafer with the deposited copper-nickel thin film.
[0022] In the above method, the gap between the quartz plates is 10-30 mm; The graphite has a length, width, and thickness of 5-8 mm, 5-8 mm, and 2-5 mm, respectively. The graphite is placed at the center of the wafer on which a copper-nickel thin film has been deposited; The slotted wafer carrier is a rectangular frame container. The slotted wafer carrier has parallel slots arranged at equal intervals on the inner wall of its frame. The quartz plate has grooves for fixing graphite.
[0023] In the above method, step (2) involves the following conditions for magnetron sputtering deposition of nickel thin films: Background vacuum less than or equal to 2 × 10⁻⁶ -5 Pa, 20-30 sccm of argon gas is introduced, the power supply is 100-150 W, and the sputtering thickness of the nickel film is 50-150 nm; In step (3), the conditions for magnetron sputtering deposition of copper thin films are as follows: Background vacuum less than or equal to 2 × 10⁻⁶ -5 Pa, 20-30 sccm of argon gas is introduced, the power supply is 100-200 W, and the sputtering thickness of the copper thin film is 250-450 nm.
[0024] In the above method, in step (1), the high-temperature annealing temperature is 1100-1200℃ and the time is 1-3 h.
[0025] In the above method, in step (4), the high-temperature annealing is carried out in a 6-inch tube furnace; Specifically, the conditions for high-temperature annealing are as follows: The 6-inch tube furnace is a three-zone tube furnace; firstly, the middle zone is heated to 650-700℃ at 20-30℃ / min, and then annealed at 1000-1100℃ at 10-15℃ / min. The heating rate of the left and right zones is the same as that of the middle zone. Throughout the heating process, the temperature of the middle zone is always kept 20-30℃ higher than that of the left and right zones. The annealing time is 2-4 hours; The annealing is carried out in a mixed atmosphere of argon and hydrogen; The annealing pressure is atmospheric pressure.
[0026] In the above method, the volume ratio of argon to hydrogen is 1-3:1; the flow rate of the mixed atmosphere is 2000-5000 sccm.
[0027] In the above method, step (3) involves cooling the temperature to 650-700°C at a rate of 5-20°C / min after high-temperature annealing, and then allowing it to cool naturally to room temperature.
[0028] In the above method, in step (4), the number of pieces is 10 or more.
[0029] Finally, the present invention provides a wafer-level stacked single-crystal boron nitride thin film prepared by the above preparation method.
[0030] The multilayered single-crystal boron nitride thin film prepared by this invention has controllable layer number, clean interface, and controllable angle. Dry bonding avoids direct contact between the boron nitride interface and the polymer and solvent, reducing the presence of contaminants at the interface of the two-dimensional material. Simultaneously, the ultra-flat single-crystal boron nitride film possesses extremely high flatness, avoiding localized damage caused by wrinkles, steps, etc., during dry bonding, effectively ensuring the integrity of the final multilayered boron nitride thin film.
[0031] Compared to traditional CVD direct growth and mechanical exfoliation methods, the method of this invention constructs multilayered single-crystal boron nitride films with ultra-high crystallinity and flatness, avoiding grain boundary and stacking disorder problems caused by heterogeneous nucleation in traditional CVD multilayer growth. Simultaneously, the use of dry transfer technology (such as PDMS / graphene-assisted transfer) completely avoids polymer residues such as PMMA found in wet transfer methods. The constructed few-layered single-crystal boron nitride films are compatible with existing semiconductor processes, providing a reliable solution for the fabrication of high-performance two-dimensional material devices. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the slot-type wafer carrier of the present invention.
[0033] Figure 2 This is a physical image of the slot-type wafer carrier of the present invention.
[0034] Figure 3 Atomic force microscopy characterization and roughness statistics of the copper-nickel alloy single-crystal wafer prepared in Example 1; wherein, Figure 3 (A) is an atomic force microscopy characterization image; (B) is a roughness statistic.
[0035] Figure 4 This is a schematic diagram of the overall process of the method of the present invention.
[0036] Figure 5 The diagram shows the structural changes of ammoniaborane before and after treatment; the left diagram is before treatment, and the right diagram is after treatment.
[0037] Figure 6 This is a mass spectrometry analysis of the ammonia borane-releasing substance with a stalactite-like structure obtained in Example 2.
[0038] Figure 7 Atomic force microscopy (AFM) morphology and height variation distribution images of boron nitride films prepared from the ammonia borane precursor before and after treatment; among them, Figure 7 In the diagram, A is the atomic force microscopy morphology characterization of the boron nitride thin film; B is the height undulation distribution diagram.
[0039] Figure 8 Physical image and Raman characterization of the hexagonal boron nitride thin film prepared in Example 3; Figure 8In the diagram, A represents a four-inch boron nitride thin film transferred onto a silicon wafer; B represents Raman spectra at nine locations on the boron nitride wafer; and C represents Raman mapping images at nine different locations on the boron nitride wafer.
[0040] Figure 9 This is a flowchart illustrating the fabrication process of stacked single-crystal boron nitride thin films.
[0041] Figure 10 Physical images of 1-5 layers of monocrystalline boron nitride thin films transferred onto a silicon wafer, along with their corresponding Raman spectra.
[0042] Figure 11 Thickness measurement diagrams for 1-5 layers of monocrystalline boron nitride thin films transferred onto a silicon wafer.
[0043] Figure 12 Statistics on the integrity of 1-5 layers of monocrystalline boron nitride films transferred onto silicon wafers, ultraviolet absorption spectra, roughness statistics, and Raman surface scanning peak positions and intensity spectra. Detailed Implementation
[0044] The present invention will be further described in detail below with reference to specific embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention.
[0045] Unless otherwise specified, the experimental methods described in the following examples are conventional methods.
[0046] Unless otherwise specified, the quantitative experiments in the following examples are all repeated three times, and the results are averaged.
[0047] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0048] The double-layered tubing used in the following embodiments includes an inner tubing and an outer tubing. The inner tubing is a quartz test tube with a diameter of 7.5 mm and a length of 5 cm; the outer tubing is a quartz test tube with a diameter of 10 mm and a length of 15 cm. The outer tubing is fitted over the inner tubing, and the opening direction of the inner tubing is opposite to that of the outer tubing. The opening of the inner tubing is placed at the bottom of the outer tubing.
[0049] The schematic diagram of the slot-type wafer carrier used in the following embodiments is shown below. Figure 1 See actual product photos Figure 2 The slot-type wafer carrier of this invention is a cuboid frame structure made of high-purity quartz material. This material selection ensures excellent stability, a low coefficient of thermal expansion, and extremely high cleanliness at temperatures exceeding 1000°C, preventing the introduction of metal contamination during annealing and thus guaranteeing the crystallization quality of the copper-nickel alloy thin film.
[0050] The slotted wafer carrier has multiple parallel slots inside for inserting quartz plates. Specific capacities are as follows: Lateral capacity: The width (W) of the carrier is designed to be slightly greater than 4 inches (approximately 120 mm), which can perfectly accommodate and hold a four-inch wafer.
[0051] Longitudinal capacity: The carrier's length (L is 400cm) is designed to accommodate three four-inch wafers side by side.
[0052] Vertical capacity: The height of the vehicle (H is 50cm) is designed to allow for the simultaneous insertion of up to 5 independent quartz plates.
[0053] Therefore, the maximum processing capacity of this carrier is 5 layers × 3 pieces = 15 four-inch wafers, achieving extremely high space utilization and batch processing efficiency.
[0054] Each support structure is a flat quartz plate with three pre-set grooves for positioning graphite blocks. The graphite blocks (5 mm × 5 mm × 3 mm) are used to support the wafers, ensuring that the wafers remain stable in the horizontal direction and preventing them from sliding, colliding or sticking during loading, unloading and annealing.
[0055] On the inner walls of both sides of the slot-type wafer carrier frame, precision parallel slots matching the thickness of the aforementioned quartz plates are machined. These slots are arranged at equal intervals, ensuring that each layer of quartz plates remains absolutely horizontal and parallel to each other after insertion, thereby guaranteeing a consistent spatial gap between layers (adjustable from 10 mm to 30 mm, specifically 30 mm in this embodiment). This gap is carefully calculated to maximize space utilization while ensuring uniform heat flow between wafers, resulting in uniform heating of all wafers. This is crucial for obtaining highly consistent single-crystal materials within a batch.
[0056] Example 1: Preparation of copper-nickel alloy single crystal wafers (1) Preparation of c-plane sapphire Ten 4-inch, single-sided polished sapphire wafers (the 4-inch single-sided polished sapphire wafers were purchased from Jiangyin Lanke Crystal Materials Co., Ltd., with a thickness of 650±25 μm) were taken and sequentially acid-washed (concentrated sulfuric acid and concentrated phosphoric acid were mixed at a volume ratio of 3:1), thoroughly rinsed with ultrapure deionized water to remove all acid residues, and dried with nitrogen.
[0057] The cleaned sapphire wafer was annealed at 1100°C for 3 hours in a pure oxygen atmosphere, and then cooled before being taken out for use.
[0058] (2) Preparation of Ni / Cu bilayer thin films by magnetron sputtering The annealed sapphire wafer was placed in a magnetron sputtering vacuum chamber and evacuated to a vacuum level of 2 × 10⁻⁶. -5Pa; then sputter a nickel target (99.99% purity), with an argon flow rate of 20 sccm, a power setting of 150 W, a sputtering time of 500 s, and a nickel layer thickness of approximately 50 nm; Switch to copper target (99.99% purity) sputtering, power set to 100 W, sputtering time 3600 s, deposited copper layer thickness approximately 450 nm; After completing the double-layer sputtering, the gas supply was stopped, the wafer was allowed to cool naturally to room temperature, and the carrier was removed to obtain a wafer with a copper-nickel thin film deposited on it.
[0059] (3) High-temperature annealing alloying and recrystallization Ten wafers with deposited copper-nickel thin films were loaded into the same slotted wafer carrier (the wafers with deposited copper-nickel thin films were placed on a quartz plate, with a graphite block placed between them, the graphite block at the center of the wafer). The carrier, along with the wafers, was placed in the central region of a 6-inch tube furnace (model: BTF-1200C-III-3ZL-CVD, Anhui Beiyike Equipment Technology Co., Ltd., three temperature zones). Under a mixed atmosphere of argon and hydrogen (argon to hydrogen volume ratio 3:1), the argon and hydrogen flow rates were 3000 scmm and 1000 sccm, respectively. The temperature of the middle temperature zone was set 30°C higher than that of the left and right temperature zones to create a temperature gradient difference during annealing, providing a driving force for the growth of single-crystal domains. First, the intermediate temperature zone is rapidly heated at a rate of 30°C / min. Then, the left and right temperature zones are opened and heated at the same rate as the intermediate zone, maintaining the temperature of the intermediate zone approximately 30°C higher than that of the left and right zones throughout the heating process. The intermediate temperature zone is heated to the recrystallization temperature of the copper-nickel metal film, 700°C, and then further heated to the annealing temperature of 1100°C at a rate of 10°C / min. The annealing time is 3 hours, and the pressure is atmospheric pressure.
[0060] After the heat preservation is completed, the three temperature zones are cooled at a rate of 10°C / min. When the middle temperature zone is cooled to 700°C, the three temperature zones are then naturally cooled to room temperature to prepare a copper-nickel alloy single crystal wafer.
[0061] Atomic force microscopy characterization and roughness statistics of the copper-nickel alloy single-crystal wafer prepared in this embodiment are shown in [reference needed]. Figure 3 .Depend on Figure 3 It can be seen that the surface roughness of copper-nickel alloy single-crystal wafers can be characterized at 10 × 10 μm. 2 The surface of the copper-nickel alloy single-crystal wafer is very smooth, with no grain boundaries. The average roughness of 40 sites on the copper-nickel wafer was also statistically analyzed, and it was only 0.45 nm, meeting the requirement of RMS < 1 nm.
[0062] Example 2: Preparation of a single-layer monocrystalline boron nitride wafer A schematic diagram of the overall process of the method of the present invention is shown below. Figure 4As shown. By controlling the decomposition products of aminoborane, polymerized aminoborane is screened out in the double-layer casing, ensuring the stable delivery of the effective precursor borazine (B3N3H6) during boron nitride wafer growth, thereby achieving the growth of ultra-flat single-layer single-crystal boron nitride wafers. The specific steps are as follows: (1) Placement of precursors and critical temperature treatment This invention uses ammonia borane (NH3·BH3) as a single BN source precursor. Under heating conditions, this substance undergoes a dehydrogenation reaction to generate the intermediate product borazine (B3N3H6), which then decomposes into boron nitride.
[0063] 100 mg of ammonia borane powder was placed at the bottom of the inner sleeve of a double-layered tubing system, with the inner sleeve inverted and placed inside the outer sleeve, the opening of the outer sleeve facing the gas inlet. The double-layered tubing was placed in a CVD tube furnace, and hydrogen gas was introduced at a flow rate of 500 sccm. The control system pressure was 200 Torr, and the ammonia borane powder placed in the double-layered tubing was heated to 130°C. After heating for 10 minutes, the powdered ammonia borane powder gradually melted and completely transformed into a stalactite-like solidified form.
[0064] After the ammonia borane solid powder has completely transformed into a stalactite-like solidified form, it is cooled to room temperature. During this process, to suppress the volatilization of the transformed product, the gas is changed to a mixture of argon and hydrogen with a volume ratio of 2:1 and a flow rate of 1000 sccm, while maintaining atmospheric pressure. After cooling to room temperature, the treated ammonia borane is removed for later use.
[0065] Electron micrographs of ammonia borane before and after treatment in a stalactite-like solidified form are shown below. Figure 5 Scanning electron microscopy revealed a significant morphological transformation of the ammoniaborane before and after treatment: it changed from a powdery structure to a stalactite-like structure. This structure remains stable over a long period and is not easily collapsed upon heating during growth, thus ensuring the stable growth of boron nitride.
[0066] The mass spectrometry analysis of the ammonia borane in the stalactite-like structure obtained above is shown in the figure. Figure 6 After pretreatment, the volatilized product is borazine molecules.
[0067] The double-layer sleeve structure effectively screens out the influence of byproduct polymerized aminoborane and effectively avoids the formation of surface particulate contaminants during boron nitride growth. It can grow uniform, low-particle-density, and highly stoichiometric h-BN films on metal substrates (such as CuNi alloy single crystals).
[0068] (2) CVD growth The treated or untreated ammonia borane precursor was placed in the upstream temperature zone of a tube furnace for h-BN film growth in a CVD tube furnace. Argon and hydrogen (argon flow rate of 500 sccm and hydrogen flow rate of 100 sccm) were introduced into the system as carrier gases, and the pressure was controlled at atmospheric pressure. The downstream growth zone was heated at a rate of 15℃ / min to 1000℃. After the downstream growth zone reached the target growth temperature, the upstream temperature zone was set up, with a heating rate of 15℃ / min to 60℃, serving as the upstream source zone. The atmosphere was then switched to hydrogen at a flow rate of 3000 sccm and the pressure was controlled at 50 Torr. An h-BN thin film was grown on the copper-nickel alloy single-crystal wafer substrate prepared in Example 1. The growth time was 10 min. After the growth was completed, all heating zones were turned off, and the atmosphere was switched to a mixed atmosphere of argon and hydrogen (argon flow rate of 500 sccm and hydrogen flow rate of 100 sccm). The pressure was controlled at atmospheric pressure. After cooling to room temperature, the single-layer single-crystal boron nitride wafer was obtained.
[0069] The effects of ammonia borane as a precursor on the surface morphology of the grown boron nitride film before and after treatment were characterized using atomic force microscopy under the same substrate growth conditions. The results are as follows: Figure 7 As shown, untreated ammonia borane, upon direct heating, produces numerous particulate contaminants on the surface of the grown boron nitride, with a roughness of 2.46 nm and significantly higher surface undulations compared to boron nitride grown with treated ammonia borane. Boron nitride grown using the treated ammonia borane precursor has a particle-free surface with a sub-nanometer roughness (0.480 nm) and undulations within 1 nm, exhibiting an ultra-smooth surface.
[0070] Meanwhile, to systematically evaluate the uniformity and crystal quality of the prepared monolayer hexagonal boron nitride (h-BN) film, it was completely transferred onto a flat silicon substrate. The four-inch diameter sample was then subjected to detailed spectroscopic characterization using a microconfocal Raman spectroscopy system. Figure 8 Nine representative locations were evenly selected at the center of the film (sampling point distribution diagram as shown in the figure). Figure 11 As shown in Figure A), its single-point Raman spectra were collected. All measurement points were within the range of ~1367 cm⁻¹. -1 A sharp and distinct Raman characteristic peak is observed nearby, which is consistent with the E in the plane of a single-layer h-BN layer. 2g The characteristic vibrational peak positions of the phonon mode match.
[0071] To further demonstrate its spatial uniformity, areas of 100 μm were selected from the above nine regions. 2 Raman mapping scans were performed on the area at ~1367 cm⁻¹. -1A two-dimensional distribution map was plotted using the peak positions as indicators. The mapping results clearly show that the Raman peak intensity distribution is highly uniform throughout the entire scanning area, and the characteristic peak positions fluctuate very little. The combined analysis of single-point spectroscopy and mapping results fully demonstrates that the growth method of this invention, using ammonia borane precursor treatment, produces monolayer h-BN films with excellent uniformity and high quality over a large area, significantly superior to traditional CVD methods that directly decompose ammonia borane to grow boron nitride.
[0072] This invention induces the formation of a stalactite-like porous microstructure in ammonia borane after preheating at a critical temperature. This structure exhibits high stability and is not easily decomposed during storage or transportation. It also possesses a highly porous network, which facilitates the uniform release of borazine gas during subsequent heating, controlling the decomposition rate and reaction window. Furthermore, by designing segmented heating zones and a double-layered sleeve for holding the ammonia borane, a slow-release platform is provided, ensuring the smooth release of precursor decomposition products. The released borazine, being gaseous molecules, is uniformly distributed in the thermal field, ensuring a stable supply to multiple sample sites simultaneously. It also limits the diffusion of non-volatile oligomer residues, preventing contamination of the growth area.
[0073] Example 3: Preparation of stacked single-crystal boron nitride thin films (1) Transfer of monolayer single-crystal boron nitride wafer: Commercially available borneol (-)-Borneol (97%) was dissolved in isopropanol solution to obtain a 25 wt% borneol solution. The borneol solution was uniformly spin-coated onto the surface of the monolayer single-crystal boron nitride wafer prepared in Example 2 using a spin coater at a speed of 1000 rpm. Then, a PMMA (polymethyl methacrylate) solution (the selected PMMA had a number average molecular weight of 950,000 and was dissolved in anisole (950K A4, Microchem Inc.) at a concentration of 4 wt%) was spin-coated at a speed of 1500 rpm. The monolayer single-crystal boron nitride wafer covered with borneol solution and PMMA solution was placed on a heating stage and baked for 10 min at a baking temperature of 180 °C. After the PMMA solidified, it was etched in a 1 mol / L ammonium persulfate solution for 6 h to remove the copper-nickel alloy and separate the boron nitride and sapphire. The detached monolayer boron nitride film is then retrieved from a silicon wafer, air-dried, and set aside for later use.
[0074] (2) Stacking of multilayer single-crystal boron nitride wafers: The single-layer single-crystal boron nitride film dried in (1) was washed in deionized water using polydimethylsiloxane tape PDMS. After natural drying, it was bonded to another single-layer single-crystal boron nitride wafer prepared in Example 2 using a roller press. Before bonding, the cleanliness of the interface must be ensured, and the bonding direction of PDMS and boron nitride wafers must be in the same direction during the roller pressing process to avoid the generation of interface bubbles. After the PDMS film with boron nitride was dry-bonded to the surface of another boron nitride wafer, the PDMS was peeled off by heating to 180°C. The PDMS was released by baking on a hot plate at a temperature of 180°C for 10 min to obtain a PMMA / borneol / hBN / hBN / copper-nickel alloy / sapphire composite structure. The wafer was then etched in a 1 mol / L ammonium persulfate solution for 6 h to remove the copper-nickel alloy and separate boron nitride and sapphire. PMMA and camphor were then removed by soaking in acetone at 80 °C to obtain a double-layer boron nitride wafer.
[0075] (3) If a multilayer (more than 2 layers) single crystal boron nitride wafer is to be prepared, the rolling bonding and etching steps of step (2) need to be repeated. PMMA and ice flakes are not removed in the middle, and they are only removed at the end after the bonding is stopped; a multilayer single crystal boron nitride thin film with a specified number of layers is obtained.
[0076] (4) Transfer of stacked single-crystal boron nitride thin film: The composite structure obtained in the last step was bonded to the target substrate using PDMS (a silicon wafer, Wafer Pro, with an oxide layer thickness of 90 nm in this embodiment). After releasing the PDMS according to the method in step (2), the film was placed in hot acetone at 80°C to remove PMMA and ice, and finally a four-inch ultra-flat stacked single-crystal boron nitride thin film was obtained.
[0077] Figure 9 This is a flowchart of the fabrication process of stacked single-crystal boron nitride thin films; specifically, it includes the process of transferring the single-layer single-crystal boron nitride wafer to PDMS through homogenization, etching, cleaning, and drying; as well as the process of bonding and transferring the wafer to the boron nitride wafer via PDMS dry bonding and finally releasing it to the target substrate, removing the polymer to obtain the stacked single-crystal boron nitride thin film.
[0078] Figure 10 Images of 1-5 layers of single-crystal boron nitride thin films transferred onto a silicon wafer, along with their corresponding Raman spectra. The Raman spectra show that as the number of boron nitride layers increases, the Raman shift wavenumber reaches 1367 cm⁻¹. -1 Characteristic peak E 2g The increase in peak intensity confirms the correlation between the number of layers in the thin film constructed using this method.
[0079] Figure 11This image shows the thickness measurements of 1-5 layers of monocrystalline boron nitride films transferred onto a silicon wafer. The thickness of boron nitride films with different numbers of layers transferred onto the silicon wafer was measured using atomic force microscopy, and the thickness showed a linear relationship with the increase of the number of layers.
[0080] Figure 12 Statistics on the integrity of 1-5 layers of single-crystal boron nitride films transferred onto silicon wafers, ultraviolet absorption spectra, roughness statistics, and Raman surface scanning peak positions and intensity spectra. Figure 12 In Figure A, the integrity of 1-5 single-crystal boron nitride films was statistically analyzed using an optical microscope. The integrity of all 1-5 layers was above 95%, which confirms the superiority of this method in constructing large-area multilayer boron nitride films. Figure 12 In section B, the characteristic absorption curves of 1-5 layer monocrystalline boron nitride films were measured using ultraviolet absorption spectroscopy. Boron nitride exhibits significant absorption in the approximately 201 nm wavelength range, and the absorbance shows a strong linear dependence with increasing layer number, demonstrating that the number of stacked boron nitride films is controllable and there is no residual adhesive between layers. Figure 12 The C value in the figure represents the roughness of 1-5 layers of single-crystal boron nitride thin films. After stacking 5 layers, the roughness of the boron nitride BAMM film is below 1 nm, exhibiting ultra-smooth characteristics. Figure 12 In the figure, D and E represent the uniformity of the five-layer monocrystalline boron nitride transferred onto the silicon wafer, characterized by Raman surface scanning. It can be seen that the Raman peaks are uniformly distributed in both position and intensity, confirming the uniformity of the constructed multilayer boron nitride.
Claims
1. A method for preparing a wafer-level stacked single-crystal boron nitride thin film, comprising the following steps: (1) Spin coat a layer of borneol onto a wafer-level monolayer single-crystal boron nitride wafer, and then spin coat a layer of polymethyl methacrylate; after the polymethyl methacrylate has cured, place it in an ammonium persulfate solution to etch away the copper-nickel alloy on the wafer-level monolayer single-crystal boron nitride wafer, so that the boron nitride and the substrate are separated, and a monolayer single-crystal boron nitride film is obtained. Alternatively, a layer of polymethyl methacrylate is spin-coated onto a wafer-level monolayer single-crystal boron nitride wafer; after the polymethyl methacrylate has cured, it is placed in an ammonium persulfate solution to etch away the copper-nickel alloy on the wafer-level monolayer single-crystal boron nitride wafer, thereby separating the boron nitride from the substrate and obtaining a monolayer single-crystal boron nitride thin film. (2) The single-layer monocrystalline boron nitride film obtained in step (1) is bonded to another wafer-level single-layer monocrystalline boron nitride wafer using a polydimethylsiloxane tape; after the polydimethylsiloxane tape is released, a composite structure is obtained; then the composite structure is placed in an ammonium persulfate solution to etch away the copper-nickel alloy, and a double-layer monocrystalline boron nitride film is obtained; the above steps are repeated until a stacked monocrystalline boron nitride film with a specified number of layers is obtained, and finally the polymer transfer medium is removed to obtain the wafer-level stacked monocrystalline boron nitride film.
2. The preparation method according to claim 1, characterized in that: The method for preparing the wafer-level monolayer single-crystal boron nitride wafer includes the following steps: S1. Heat the ammonia borane powder in a hydrogen atmosphere at 120~140℃ to obtain ammonia borane with a stalactite-like structure. S2. Using the stalactite-like structured ammonia boronane crop precursor, a boron nitride thin film is prepared by chemical vapor deposition.
3. The preparation method according to claim 2, characterized in that: In step S1, the heating treatment time is 10~15 min; The temperature of the heat treatment is 130±5℃.
4. The preparation method according to claim 2 or 3, characterized in that: Step S1 includes the following steps: placing ammonia borane powder at the bottom of the inner sleeve of the double-layered tube, turning the opening of the outer sleeve towards the gas inlet direction, introducing hydrogen gas, and heating to 130±5℃ for treatment to obtain ammonia borane with a stalactite-like structure.
5. The preparation method according to claim 4, characterized in that: The double-layered sleeve includes an inner sleeve and an outer sleeve, both of which are test tubes open at one end; the outer sleeve is fitted over the inner sleeve, and the opening directions of the outer sleeve and the inner sleeve are opposite. The diameter ratio of the inner sleeve to the outer sleeve is 1:2 to 3:4; The outer sleeve is longer than the inner sleeve.
6. The preparation method according to claim 4, characterized in that: The hydrogen flow rate is 300~500 sccm; The system pressure is 200~300 Torr; Step S1 also includes the step of heating and then cooling to room temperature; During the cooling process, the introduced gas is replaced with a mixture of argon and hydrogen; the system pressure is atmospheric pressure.
7. The preparation method according to claim 6, characterized in that: In the mixed gas during the cooling process, the volume ratio of argon to hydrogen is 1:1 to 3:1; The flow rate of the mixed gas is 500~2000 sccm.
8. The preparation method according to claim 2, characterized in that: In step S2, chemical vapor deposition is performed on a wafer-level copper-nickel alloy wafer.
9. The wafer-level stacked single-crystal boron nitride thin film prepared by the preparation method according to any one of claims 1-8.
Citation Information
Patent Citations
Preparation method of wafer-level and high-quality boron nitride / graphene heterojunction film
CN112159970A
High-quality wafer-level single-crystal multilayer boron nitride film and controllable preparation method and application thereof
CN116265625A
